2019
DOI: 10.1016/j.adro.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Quality of Life After Radiation Therapy for Oropharyngeal Carcinoma

Abstract: PurposeSubstantial research exists on the physical toxicities from radiation therapy (RT) for oropharyngeal cancers, but emotional quality of life is understudied. The purpose of this study is to map the effects and time course of radiation-related changes in mood and anxiety and to investigate the physical factors that drive these changes.Methods and materialsWe prospectively collected University of Washington Quality of Life questionnaires and identified patients with oropharyngeal cancer who were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Janz’s prospective cohort study exploring differences between HPV-associated OPSCC patients (n = 21) and HPV-negative oral cavity cancer patients who smoke (n = 17) found that, at 12 months, the HPV-associated OPSCC cohort had an improved depression score on the CES-D [ 28 ]. Rajeev-Kumar conducted a retrospective analysis of OPSCC patients treated with RT (n = 69) using the University of Washington QOL (UW-QOL) questionnaire and noted that anxiety and mood scores improved at 12 months compared to pre-treatment values [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Janz’s prospective cohort study exploring differences between HPV-associated OPSCC patients (n = 21) and HPV-negative oral cavity cancer patients who smoke (n = 17) found that, at 12 months, the HPV-associated OPSCC cohort had an improved depression score on the CES-D [ 28 ]. Rajeev-Kumar conducted a retrospective analysis of OPSCC patients treated with RT (n = 69) using the University of Washington QOL (UW-QOL) questionnaire and noted that anxiety and mood scores improved at 12 months compared to pre-treatment values [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies did not associate worsening mental health with HPV status (Qualliotine on CES-D initial screen, Rajeev-Kumar on UW-QOL, and Shinn using both the PHQ-9 and the CES-D) [ 29 , 31 , 34 ]. Shinn performed a prospective cohort study on 130 patients with OPSCC [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, almost all patients experience a significant loss of taste acuity at a dose of 60 Gray. Dysgeusia typically occurs within 3-4 weeks of treatment and some studies have shown complete recovery within 3-12 months, depending on the volume of the irradiated tissues [6,12,15,16]. Especially moderate taste alterations start during the 2nd week of RT, involving 40% of patients, while severe dysgeusia is experienced from the 3rd week onward, reaching the peak of rate and severity of symptoms in the 5th week [11].…”
Section: Radiation Therapymentioning
confidence: 99%
“…Especially moderate taste alterations start during the 2nd week of RT, involving 40% of patients, while severe dysgeusia is experienced from the 3rd week onward, reaching the peak of rate and severity of symptoms in the 5th week [11]. Unfortunately, some patients exhibit incomplete or no recovery even several years later [6,12,15,16]. Indeed, significant worsening of taste function both at short (within 1 year) and long term (up to 11 years) follow-up was shown in survival and non-survival patients with OSCC who have undergone adjuvant RT, compared to the baseline [6,17,28].…”
Section: Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation